2018
DOI: 10.24198/jbm.v19i2.189
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout: A Mediation between Emotional Intelligence and Turnover Intention

Abstract: The emotional intelligence of employees can make employees have the desire to the turnover intention which can also be influenced by the level of job burnout employees. This research aims to investigate the effect of emotional intelligence on the turnover intention with job burnout as the mediating variable. This study uses a quantitative analysis method which aims to analyze the relationship between the observed variables and to confirm the theory using PLS-SEM analysis (Partial Least Square-Structural Equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Burnout is a form of physical, emotional, and mental exhaustion that occurs in someone who is in a situation full of long-term emotional demands (Kartono & Hilmiana, 2018). Ayu & Dharmapatni (2019) explained that burnout refers to the loss of interest and job satisfaction due to stressful working conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burnout is a form of physical, emotional, and mental exhaustion that occurs in someone who is in a situation full of long-term emotional demands (Kartono & Hilmiana, 2018). Ayu & Dharmapatni (2019) explained that burnout refers to the loss of interest and job satisfaction due to stressful working conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rahim and Cosby [ 79 ] showed that there exists a direct relationship, linking burnout and turnover intention about the ancillary effect of burnout on the turnover intention with work engagement acting as the partial mediator. Kartono and Hilmiana [ 80 ] showed that job burnout positively impacts the turnover intention. This is contemplated in the job burnout indicators, namely declining work performance, depersonalization, and exhaustion [ 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study demonstrated that emotional exhaustion and depersonalisation are significantly positively related to turnover intention, while personal accomplishment is significantly negatively related to the outcome variable. Many other studies confirmed the relationship between burnout and turnover intention across different job functions and countries, for example South African ICT employees (DuPlooy & Roodt, 2010), Indonesian banking employees (Kartono & Hilmiana, 2018) and Indonesian auditors (Santoso et al, 2018).…”
Section: Relationship Between Burnout and Turnover Intentionmentioning
confidence: 81%
“…According to Mor Barak et al (2001, p. 653), burnout is one of the best predictors of turnover in the human service professions, while job performance and absenteeism are important antecedents of turnover in most other occupations. However, many studies found evidence that burnout is not only related to turnover intention in the human service professions (Scanlan & Still, 2013), but also in other occupations that are not related to these professions (Chan, Wan, & Kuok, 2015;DuPlooy & Roodt, 2010;Kartono & Hilmiana, 2018;Kaatz, French, & Prentiss-Cooper, 1999, pp. 169-170;Santoso et al, 2018).…”
Section: Relationship Between Burnout and Turnover Intentionmentioning
confidence: 99%